Caracterización físico – química de los principales humedales de Jalca de la concesión para conservación Alto Huayabamba - Navarro Cahuaza, Alexis (2012)
The Concession for Conservation High Huayabamba, its extension includes two ecoregions as is the Jalea and Yunga that is located at the headwaters of the right margin of the Huayabamba river, an important tributary of the Huallaga River in the San Martín region; it is in this conservation area where the investigation work was realized called "physicochemical characterization of the Jalea principal wetlands of the Concession for Conservation High Huayabamba, 2012 ", the present work had as aims identify Jalea principal wetlands of the CCAH, determine the chemical characteristics ( dissolved oxygen, pH, Ammonium and Nitrates) of the principal wetlands of Jalea, determine the physical characteristics (Temperature, electrical Conductivity) ofthe principal wetlands of Jalea and to evaluate the results to define the postulation of Jalea wetlands of the CCAH to Ramsar Convention. The area of study was the ecoregion Jalea in the wetlands that exist in this zone (Lagoons, rivers and bogs or marshes). In the present research work was conducted in two different times, during the rainy season (March and April) and dry season (June and July), it was characterized to a total of 28 wetlands distributed in four (04) sectors such as: Huayabamba, Yonán, Quinguyacu and Yampio In these sectors was made fifty-two (52) samples, 11 samples in Huayabamba, 13 samples in Yonan, 12 samples in Yampio and 16 samples in Quinguyacu, the basic analyzed parameters were Temperature, dissolved oxygen, hydrogen potential, Ammonium, Nitrate and electrical Conductivity. Ofthe realized study it is clear that the chemical parameters that suffer alteration are the pH and the NH4 ofthe rivers (general average), many are the factors that affect the pH since it is an excess of absorption of ions on cations, in addition to the constant rainfall allow the increase of it. With regard to the concentration of ammonium they are originated by metabolic processes as the agriculture, the cattle activity that is the case ofthis place, which increases his level of concentration.